Stretching the Bounds: Nematic Liquid Crystal Tactoids in Applied Electric Fields - Wennerholm, Cole E. (Tufts Archival Research Center, 2022)
In contrast to isotropic fluids, liquid crystals can sustain elastic deformations and order-dependent surface tension. Hence, equilibrium shapes of liquid crystal droplets (known as a tactoid) are much richer than the spherical shapes adopted by isotropic fluids. Here, we consider the problem of a nematic liquid crystal droplet deformed by an imposed electric field. Finite element simulations are presented to determine the droplet shape as a function of the electric field, anchoring conditions and the elastic properties of the material. Our simulation method allows us to features like cusps that are challenging with other methods. Prospects for simulation of tactoids involving other kinds of liquid crystal phase will also be discussed.; Thesis (B.S.)--Tufts University, 2022.; Submitted to the Dept. of Physics and Astronomy.